2015
DOI: 10.3906/sag-1404-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of changes in muscle strength in gestational ageupon fear of falling and quality of life

Abstract: The aim of this study is the investigation of the effect of changes in muscle strength in gestational age upon fear of falling and quality of life. Materials and methods:This longitudinal, descriptive study included a sample of 37 pregnant women who volunteered to participate. The research data were collected at 20 and 32 weeks of gestation. Data collection instruments included a newly developed questionnaire form, the Tinetti Falls Efficacy Scale, a visual analog scale, and the Turkish language version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 23 publications
1
26
3
Order By: Relevance
“…Apart from tendon properties we did not observe any effect of pregnancy on the knee extensor muscle strength. This is contrary to Atay and Basalan Iz (2015) reporting a 9% reduced handgrip strength at the end of pregnancy compared to the values being measured during the middle of pregnancy. The deviating findings may indicate that the upper and lower extremities undergo different adaptation processes during pregnancy.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Apart from tendon properties we did not observe any effect of pregnancy on the knee extensor muscle strength. This is contrary to Atay and Basalan Iz (2015) reporting a 9% reduced handgrip strength at the end of pregnancy compared to the values being measured during the middle of pregnancy. The deviating findings may indicate that the upper and lower extremities undergo different adaptation processes during pregnancy.…”
Section: Discussioncontrasting
confidence: 96%
“…The deviating findings may indicate that the upper and lower extremities undergo different adaptation processes during pregnancy. While loss in handgrip strength has been suggested to be primarily related to a reduced physical activity level (Atay and Basalan Iz, 2015) we may argue that leg strength has been maintained due to the pregnancy induced increase in body mass.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, no study has yet investigated lower limb muscles during pregnancy. A study on upper limb muscles has observed a 9% decline in handgrip strength in the late stage of pregnancy compared to the middle stage of pregnancy (Atay and Basalan Iz, 2015). It is possible that both the upper and lower body are subjected to different adaptation processes during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only two studies investigating changes in strength of the upper and lower extremities with pregnancy. One study investigated changes in the hand grip strength in pregnant women, detecting a 9% loss in strength in the late stage of pregnancy compared to the middle stage of pregnancy (Atay and Basalan Iz, 2015). Another study conducted measurements of the lower and upper body strength before pregnancy and 6 weeks postpartum (Treuth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation